Hst observations of the field star population in the large magellanic cloud - Elson, Rebecca A.W. (1997)
We present V and I photometry, obtained with the Hubble Space Telescope, for ~ 15 800 stars in a field in the inner disc of the Large Magellanic Cloud. We confirm previous results indicating that an intense star formation event, probably corresponding to the formation of the LMC disc, occurred a few times 109 yr ago. We find a small but real difference between our field and one further out in the disc observed by Gallagher et al.: either star formation in the inner disc commenced slightly earlier, or the stars are slightly more metal-rich. We also find evidence for a later burst, around 1 Gyr ago, which may correspond to the formation of the LMC bar. About 5 per cent of the stars in our field are substantially older than either burst, and are probably members of an old disc or halo population with age ~ 12 Gyr.